Odpowiedź :
[tex]f(x) = (-6k+3)x + k - 2\\\\P(-3, 2) \ \ \rightarrow \ \ x = -3, \ \ y = 2\\\\2 = (-6k+3)\cdot(-3)+k-2\\\\2 = 18k-9 + k - 2\\\\2 = 19k - 11\\\\19k = 2+11\\\\19k = 13 \ \ /:19\\\\\underline{k = \frac{13}{19}}[/tex]
ax + b - postać lkierunkowa funkcji liniowej
a - współczynnik kierunkowy
b - wyraz wolny
[tex]f(x) = (-6k+3)x + k - 2\\\\a = -6k+3\\\\a = -6\cdot\frac{13}{19} + \frac{3\cdot19}{19}\\\\a = -\frac{78}{19} + \frac{57}{19}\\\\\underline{a = -\frac{21}{19} = -1\frac{2}{19}}[/tex]